CORSIA: The first internationally adopted approach to calculate life-cycle GHG emissions for aviation fuels. (October 2021) - Prussi, Matteo; Lee, Uisung; Wang, Michael; Malina, Robert; Valin, Hugo; Taheripour, Farzad; Velarde, César; Staples, Mark D.; Lonza, Laura; Hileman, James I.
Abstract: The aviation sector has grown at a significant pace in recent years, and despite improvements in aircraft efficiency, the sector's impact on climate change is a growing concern. To address this concern, the International Civil Aviation Organization (ICAO) established the Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) to help reduce aviation greenhouse gas (GHG) emissions. This paper presents a methodology agreed by the 193 ICAO member states to evaluate the life-cycle GHG emissions of sustainable aviation fuels (SAFs), in the CORSIA system. The core life-cycle assessment and induced land use change values of SAFs are presented to determine the GHG savings of certified pathways. The paper aims to present that a number of SAFs can yield significant life-cycle emission reductions compared to petroleum-derived jet fuel. This implies the potentially major role of SAFs in reducing aviation's carbon footprint. Highlights: The goal of the CORSIA is to reduce GHG emissions from international aviation. Internationally agreed LCA methodologies for GHG saving potentials are presented. Sustainable aviation fuels can reduce GHG emissions up to 90%. SAFs GHG saving can exceed 100% when land use change is included. Further challenges for reducing the GHG emissions from aviation are discussed.